Anti-EGFR therapy in metastatic colorectal cancer: mechanisms and potential regimens of drug resistance. (23rd June 2020) - Li, Qing-Hai; Wang, Ying-Zhao; Tu, Jian; Liu, Chu-Wei; Yuan, Yu-Jie; Lin, Run; He, Wei-Ling; Cai, Shi-Rong; He, Yu-Long; Ye, Jin-Ning
Abstract: Cetuximab and panitumumab, as the highly effective antibodies targeting epidermal growth factor receptor (EGFR), have clinical activity in the patients with metastatic colorectal cancer (mCRC). These agents have good curative efficacy, but drug resistance also exists at the same time. The effects of KRAS, NRAS, and BRAF mutations and HER2 amplification on the treatment of refractory mCRC have been elucidated and the corresponding countermeasures have been put forward. However, the changes in EGFR and its ligands, the mutations or amplifications of PIK3CA, PTEN, TP53, MET, HER3, IRS2, FGFR1, and MAP2K1, the overexpression of insulin growth factor-1, the low expression of Bcl-2-interacting mediator of cell death, mismatch repair-deficient, and epigenetic instability may also lead to drug resistance in mCRC. Although the emergence of drug resistance has genetic or epigenetic heterogeneity, most of these molecular changes relating to it are focused on the key signaling pathways, such as the RAS/RAF/mitogen-activated protein kinase or phosphatidylinositol 3-kinase/Akt/mammalian target of the rapamycin pathway. Accordingly, numerous efforts to target these signaling pathways and develop the novel therapeutic regimens have been carried out. Herein, we have reviewed the underlying mechanisms of the resistance to anti-EGFR therapy and the possible implications in clinical practice.